Integration of Quranic Values in Learning Strategies: Review of Interpretation and Implementation - Saputra, Reza Aprian; Subki, Subki (Fitrah: Journal of Islamic Education, 2024)
The integration of Qur'anic values in learning strategies is important for successful learning, but there is often a misunderstanding of the values contained in the Qur'an. With regard to that, this study aims to analyze the integration of Qur'anic values in learning strategies, focusing on verses related to learning, namely surah al-Alaq verses 1-5, Taha verse 114, al-Mujadilah verse 11, an-Nahl verse 125, an-Nur 30-31. Implementation of values at MTs. Mizabul Ulum West Lombok is the focus of research. Qualitative methods with thematic interpretation and descriptive analysis were used, as well as observation, interviews, and documentation studies as data collection techniques. The research findings show that Qur'anic values, such as the importance of reading, educational aids, patience, tolerance, and justice, underlie learning strategies. The implementation of lectures, discussions and habituation effectively support students' character building and understanding. Implementation challenges include lack of understanding and practical guidelines. This research has implications for the integration of Qur'anic values in learning strategies that improve learning quality and shape student character according to Islamic teachings. Results support Jean Piaget's theory of constructivism which emphasizes learning not only memorizing, but also internalizing values.